The effectiveness of aerobic exercise for pain management in patients with fibromyalgia - Denisa Manojlović; Eva Ivana Kopše (PAGEPress Publications, 2023)
The effectiveness of exercise therapy is being increasingly studied in patients with fibromyalgia. The aim of our systematic review was to determine the effectiveness of different types of aerobic exercise programs for pain management in patients with fibromyalgia. The literature search was performed by two independent researchers in the PubMed, CINAHL and PEDro databases using various combinations of the following keywords: fibromyalgia, pain and aerobic exercise. Studies were eligible if they included adults diagnosed with fibromyalgia and examined the effectiveness of at least one aerobic exercise program on pain management. A total of 14 randomized controlled trials were screened in full-text, nine of which were included in the systematic review. Overall, our results indicate that aerobic exercise is effective for pain management in patients with fibromyalgia. The results of the aerobic exercise programs were more effective for pain management than stretching exercises, but did not differ significantly from those of pilates, muscle strengthening exercises, relaxation techniques and stress management treatment. Additional high-quality studies are warranted to determine accurate clinical guidelines in terms of aerobic exercise programs for pain management in patients with fibromyalgia.